A critical review of the biopsychosocial model of low back pain care: time for a new approach?. Issue 13 (19th June 2022) - Mescouto, Karime; Olson, Rebecca E.; Hodges, Paul W.; Setchell, Jenny
Abstract: Purpose: Low back pain (LBP) is the leading cause of disability worldwide. Clinical research advocates using the biopsychosocial model (BPS) to manage LBP, however there is still no clear consensus regarding the meaning of this model in physiotherapy and how best to apply it. The aim of this study was to investigate how physiotherapy LBP literature enacts the BPS model. Material and methods: We conducted a critical review using discourse analysis of 66 articles retrieved from the PubMed and Web of Science databases. Results: Analysis suggest that many texts conflated the BPS with the biomedical model [Discourse 1: Conflating the BPS with the biomedical model]. Psychological aspects were almost exclusively conceptualised as cognitive and behavioural [Discourse 2: Cognition, behaviour, yellow flags and rapport]. Social context was rarely mentioned [Discourse 3: Brief and occasional social underpinnings]; and other broader aspects of care such as culture and power dynamics received little attention within the texts [Discourse 4: Expanded aspects of care]. Conclusion: Results imply that multiple important factors such as interpersonal or institutional power relations, cultural considerations, ethical, and social aspects of health may not be incorporated into physiotherapy research and practice when working with people with LBP. IMPLICATIONS FOR REHABILITATION: When using the biopsychosocial model with patients with low back pain, researchers narrowly focus on biological and cognitive behavioural aspects of the model. Social and broader aspects such as cultural, interpersonal and institutional power dynamics, appear to be neglected by researchers when taking a biopsychosocial approach to the care of patients with low back pain. The biopsychosocial model may be inadequate to address complexities of people with low back pain, and a reworking of the model may be necessary. There is a lack of research conceptualising how physiotherapy applies the biopsychosocial model in research and practice.